2018
DOI: 10.1108/rpj-02-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Layerwise monitoring of electron beam melting via backscatter electron detection

Abstract: Purpose The purpose of this study is the introduction and validation of a new technique for process monitoring during electron beam melting (EBM). Design/methodology/approach In this study, a backscatter electron detector inside the building chamber is used for image acquisition during EBM process. By systematic variation of process parameters, the ability of displaying different topographies, especially pores, is investigated. The results are evaluated in terms of porosity and compared with optical microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 9 publications
(18 reference statements)
1
32
0
Order By: Relevance
“…Numerical predictions are only useful, when the applied software was previously validated with experimental results. Four different SEBM machines (Arcam AB: Arcam A2, A2X, Q10, ATHENE (modified S12) [7] ) are applied to manufacture test samples and parts of various alloys (titanium, nickel, or aluminum alloys). A bunch of measurement devices allow to detect porosity, layer binding defects, alloy concentration, and microstructure.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical predictions are only useful, when the applied software was previously validated with experimental results. Four different SEBM machines (Arcam AB: Arcam A2, A2X, Q10, ATHENE (modified S12) [7] ) are applied to manufacture test samples and parts of various alloys (titanium, nickel, or aluminum alloys). A bunch of measurement devices allow to detect porosity, layer binding defects, alloy concentration, and microstructure.…”
Section: Applicationsmentioning
confidence: 99%
“…One strategy for process optimization is to use in situ real-time measurement systems to adjust parameters during the process, to circumvent defects. [7][8][9] Nevertheless, for a controllable, predictable, and reliable process, it is necessary to understand the underlying physical mechanisms during powder deposition, melting, and solidification in each layer, to derive optimal process strategies. Experiments allow only limited access to quantities such as spatial temperature evolution, melt pool dynamics, and solidification pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez et al [5] analysed the in-process thermal images histogram of the EBM processing area to distinguish between components with uniform temperature and that with cold spots. Arnold et al [6] evaluated the topography and porosity of an EBM manufactured component by comparing the in-process electronic images with post-process CT scans and images from an optical microscope. The data analysis attempts described so far have shown that no methodologies involve the evaluation of in-process images against reference images generated from STL models.…”
Section: Technology Gap In Stl-image Generation For Quality Evalaitonmentioning
confidence: 99%
“…It was shown that electron optical (ELO) images may be obtained using the electron beam in a way comparable with scanning electron microscopy. [13,14] By recording the topography of the molten surfaces, it was demonstrated that image features and defects inside the final sample may be correlated [13] and that this finding may be used to deduce processing windows in a fast and reliable manner. [15] The installed BSE detector was robust against elevated temperatures, metallization, and X-ray radiation and delivered high-contrast images.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were conducted using the ATHENE system and its integrated BSE detection hardware. A more detailed description of this in-house developed EBM system can be found in Arnold et al [13] In a first experiment, single-square-shaped areas with a size of 15 mm  15 mm were molten on a base-plate made of X15CrNiSi20-12 stainless steel at room temperature. The experiment was supposed to deliver basic information about electron backscattering during melting without considering the complex conditions of an EBM process, for example, the interaction between beam and powder bed.…”
Section: Introductionmentioning
confidence: 99%